2010
DOI: 10.1002/mde.1493
|View full text |Cite
|
Sign up to set email alerts
|

R&D and Tobin's q in an emerging financial market: the case of the Athens Stock Exchange

Abstract: New insight into the biogenetic origin of stenusine 1, the spreading agent of the beetle Stenus comma, is gained from the results of a one‐pot synthesis of the natural and the racemic compound [Eq. (1)]. On the basis of these results a plausible biogenetic pathway to 1 is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…At first we considered the time lag effect of R&D investments on financial performance. As documented by Parcharidis and Varsakelis (2010), Mezghanni (2011) and Zhang et al (2014), R&D investments are long-term projects and so they take time to prosper and produce positive results on corporate performance and profitability. Thus, following the above mentioned studies both models were re-estimated using 1 and 2 year lags of the R&D investments and expenses variables.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At first we considered the time lag effect of R&D investments on financial performance. As documented by Parcharidis and Varsakelis (2010), Mezghanni (2011) and Zhang et al (2014), R&D investments are long-term projects and so they take time to prosper and produce positive results on corporate performance and profitability. Thus, following the above mentioned studies both models were re-estimated using 1 and 2 year lags of the R&D investments and expenses variables.…”
Section: Resultsmentioning
confidence: 99%
“…First, the majority of studies on this topic have been focusing on rather stable periods and these results could not be generalized during economic recessions (Lome et al, 2016). Also, we extend the study by Parcharidis and Varsakelis (2010) by considering the capitalization of R&D in non-listed companies' balance sheets and not only R&D expenses, since firms that capitalize R&D tend to expect future long-term economic benefits from such projects. Our study is free from such survivorship bias by including the vast majority of corporations is Greece utilizing 3,332 firmyear observations.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Olibe, (2010); Parcharidis and Varsakelis, (2010); and Gupta et al, (2017) pointed out that there is a positive relationship between R&D intensity and firm value. On the other side, Kim et al, (2018), andNaik et al, (2012) indicated that relation between R&D and firm value takes U shape.…”
Section: Introductionmentioning
confidence: 99%